Regional analysis of ex-situ water harvesting: Potential for expansion in South Asia - Ag Water Solutions, Inc. (International Water Management Institute, 2012)
South Asia (SA), including India, Pakistan, Bangladesh, Sri Lanka, Nepal, and Bhutan, is one of the most populous regions in the world. Agriculture is the backbone of the economies of SA nations and is the main source of livelihood for many rural poor households. While parts of SA have experienced considerable agricultural sector growth in the last half-century, other areas, including large parts of eastern India and Bangladesh, have lagged behind. Many farmers face water scarcity due to both physical constraints as well as lack of adequate water storage and management. Inability to access or control water has a direct impact on agricultural productivity and reduces the potential payoff from other productivity-increasing inputs, such as fertilizers and improved seeds. Furthermore, climate variability is one of the most influential factors affecting agricultural production, and long-term climate change raises concerns about the future feasibility of irrigated agriculture in the region.